A study on spatial filtering of a speckle image reflected from a scattering medium in a coherent beam combining system - Park, Jaedeok; Choe, Yunjin; Yeom, Dong Il (Journal of the Korean Physical Society, 2021)
We conducted a study to explore a real-time monitoring variable of a coherently combined beam returned from a scattering target. The effect of a spatial filtering on the speckle pattern generated from the interference of the scattered beam was examined in a coherent beam combining (CBC) system, including three-channel laser output, the scattering target, and receiver optics in free space. We were able to recognize the arrangement of the original beams from the speckle pattern by applying a proper spatial filter with a size of 2 mm. The power-in-the-bucket value in the monitoring system was also investigated as a function of the spatial filter size. Our research implies that a complex speckle pattern can be analyzed using spatial filtering to derive a single-output real-time variable in the CBC monitoring system.
Keywords: Fiber lasers; Fourier optics; Laser beam combining; Speckle